Individual differences and political contexts: the role of personality traits and direct democracy in explaining political protest - Ackermann, Kathrin (Swiss political science review, 2017)
Building on a growing literature concerned with the link between psychological dispositions and political protest behavior, we argue that this relationship is not universal, but rather depends on contextual factors. Political context factors are able to alter the meaning and understanding of participatory repertoires. This, in turn, leads to differential effects of personality on participation. We argue that direct democracy constitutes such a political context that can act as moderating factor with regard to protest participation. In order to test this interaction between person and situation empirically, we conduct a subnational comparative analysis of the Swiss cantons. Hierarchical regression models reveal that the personality traits openness to experience and extraversion affect protest behavior directly. Most importantly, however, the link between openness to experience and protest participation is significantly moderated by direct democracy. This provides evidence for variance in the situational expression of personality traits.
First published: 15 November 2016
Gesehen am 14.04.2021